CD28-CD80 interactions control regulatory T cell motility and immunological synapse formation(,) - Thauland, Timothy J. (J Immunol, 2014)
Regulatory T cells (Tregs) are essential for tolerance to self and environmental antigens, acting in part by downmodulating costimulatory molecules on the surface of dendritic cells (DCs) and altering naïve CD4 T cell-DC interactions. Here, we show that Tregs form stable conjugates with DCs before, but not after, they decrease surface expression of the costimulatory molecule CD80 on the DCs. We use supported planar bilayers to show that Tregs dramatically slow down, but maintain a highly polarized and motile phenotype after recognizing antigen in the absence of costimulation. These motile cells are characterized by distinct accumulations of LFA-1-ICAM-1 in the lamella and TCR-MHC in the uropod, consistent with a motile immunological synapse or ‘kinapse’. However, in the presence of high, but not low, concentrations of CD80, Tregs form stationary, symmetrical synapses. Using blocking antibodies, we show that, while CTLA-4 is required for CD80 downmodulation, CD28-CD80 interactions are critical for modulating Treg motility in the presence of antigen. Together, these results support the hypothesis that Tregs are tuned to alter their motility depending on costimulatory signals.